The Importance of Artificial Wetlands in the Conservation of Wetland Birds and the Impact of Land Use Attributes Around the Wetlands: a Study from the Ajara Conservation Reserve, Western Ghats, India - S. Patil; K. Choudaj (Zoodiversity, 2023)
Artificial wetlands are built to meet the rising human population's water needs, with little attention paid to their ecological significance. The current study was carried out to assess the importance of artificial wetlands in biodiversity conservation. Habitat quality of wetlands was assessed using the birds as an ecological indicator. Bird surveys were carried out at the five artificial wetlands located in the Ajara conservation reserve, northern Western Ghats, India. Bird surveys were conducted for five years (2011–2015). During the study, 165 bird species were recorded, including 34 wetland birds and 131 wetland-associated birds. Wetlands in forested areas have a higher richness of wetland birds. Wetlands surrounded by exotic plantations, agriculture, and human settlements exhibit lower wetland bird richness than wetlands in forested areas. Land use attributes around the wetlands affect wetland bird diversity. The current study gives a glimpse that these artificial wetlands could serve as a possible habitat for wetland birds.